2021
DOI: 10.1101/2021.04.06.21254949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suboptimal response to COVID-19 mRNA vaccines in hematologic malignancies patients

Abstract: Studies describing SARS-CoV-2 immune responses following mRNA vaccination in hematology malignancy (HM) patients are virtually non-existent. We measured SARS-CoV-2 IgG production in 67 HM patients who received 2 mRNA vaccine doses. We found that 46% of HM patients did not produce antibodies and were therefore vaccine non-responders. Patients with B-cell CLL were at a particularly high risk, as only 23% had detectable antibodies despite the fact that nearly 70% of these patients were not undergoing cancer thera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
120
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(133 citation statements)
references
References 14 publications
(17 reference statements)
9
120
1
Order By: Relevance
“…As suggested by different authorities (e.g., UK Joint Committee on Vaccination and Immunisation), individuals with immunosuppression should be prioritized for the COVID-19 vaccination [ 27 ]. However, on the other hand, these individuals may reveal a diminished response to the vaccine, while some, as confirmed for two cases reported in our study, could be subject to vaccine failure [ 17 ]. Therefore, it is pivotal to advise these patients to continue to adhere to preventive measures, particularly at a time of a high number of infections in the population, and to test the serum level of anti-SARS-CoV-2 IgG antibodies following the vaccination.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As suggested by different authorities (e.g., UK Joint Committee on Vaccination and Immunisation), individuals with immunosuppression should be prioritized for the COVID-19 vaccination [ 27 ]. However, on the other hand, these individuals may reveal a diminished response to the vaccine, while some, as confirmed for two cases reported in our study, could be subject to vaccine failure [ 17 ]. Therefore, it is pivotal to advise these patients to continue to adhere to preventive measures, particularly at a time of a high number of infections in the population, and to test the serum level of anti-SARS-CoV-2 IgG antibodies following the vaccination.…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, reduced immunogenicity after a single dose and after the full vaccination regime must be taken into account in the case of some elderly subjects, cancer patients, and other immunocompromised individuals [ 14 , 15 , 16 ]. Importantly, some of these vaccine recipients may not produce any antibodies and may remain highly susceptible to the SARS-CoV-2 infection [ 17 ]. The exact percentage of individuals falling into the non-responders category is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is encouraged in these immunosuppressed patient groups, although it is possible that the immune responses will be less robust, as has been seen in response to natural infection. 152 153 Indeed, early studies are showing comparable safety, but reduced immunogenicity has been observed for these populations, including patients with HM, 154–156 SOTRs, 157 and those with rheumatological diseases. 158 159 To achieve comparable vaccine efficacy, further strategies employing altered vaccine schedules, doses, or adjustment to immunosuppression during vaccination might be needed, and should be accomplished only in the context of a clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals with a compromised immune system, including transplant patients, patients with cancer and individuals taking immunosuppressive drugs, do not mount strong responses to vaccines, including those for SARS-CoV-2 [5][6][7][8] . At present, the messaging from regulatory agencies states that "antibody tests should not be used to evaluate a person's level of immunity or protection from COVID-19. "…”
Section: Florian Krammermentioning
confidence: 99%